Effects of different temperatures on photosynthesis and rooting of Cupressus gigantea seedlings - XIN Fumei; WANG Yuting; LI Shengmao; Danzengluobu; Pubuciren (浙江大学学报. 农业与生命科学版)
The Cupressus gigantea seedlings were cultivated under different temperatures (7.5, 12.5, 17.5, 22.5, 27.5 ℃) through artificial weather boxes, and the effects of different temperatures on growth, development and photosynthesis of seedlings were investigated. The results showed that: 1) Different temperatures significantly affected the growth of C. gigantea seedlings. The seedling height, aboveground dry mass, underground dry mass, new root dry mass and new root number reached the maximum at the temperature of 17.5 ℃, followed at 12.5 and 22.5 ℃, and they were poor at 27.5 and 7.5℃ (P<0.05). 2) The photosynthesis of the C. gigantea seedlings was different under the different temperatures. The net photosynthetic rate, stomatal conductance and transpiration rate reached the maximum, and the intercellular CO2 concentration was the smallest at 17.5 ℃, but on the contrary at 7.5℃ . 3) The biomass of the new root was the highest at 17.5℃ (P<0.05), which was significantly higher than the other temperatures. While, the new root biomass was very small at 7.5 ℃, only accounted for about 1/5of biomass at 17.5 ℃. The new root length, surface area and volume were relatively large at 17.5 and 22.5℃ compared with the other temperatures. The new root specific length was larger at 7.5 and 27.5℃ than at 12.5, 17.5 and 22.5 ℃, and the difference between the three temperatures was not significant. The above results show that the growth, development and photosynthesis of C. gigantea are different under the different temperatures, and the relative suitable growth temperature is 17.5 ℃, while the relative high temperature and relative low temperature are not conducive to its photosynthesis and the growth of new rooting.